2015
DOI: 10.1021/acs.inorgchem.5b00881
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Transition-Metal-Catalyzed Reduction of Molecular Dinitrogen under Ambient Reaction Conditions

Abstract: This paper describes our recent progress in catalytic nitrogen fixation by using transition-metal-dinitrogen complexes as catalysts. Two reaction systems for the catalytic transformation of molecular dinitrogen into ammonia and its equivalent such as silylamine under ambient reaction conditions have been achieved by the molybdenum-, iron-, and cobalt-dinitrogen complexes as catalysts. Many new findings presented here may provide new access to the development of economical nitrogen fixation in place of the Habe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
144
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(153 citation statements)
references
References 112 publications
4
144
1
1
Order By: Relevance
“…17). 61,157,191,192,41,44,165 Peters has shown that phosphine ligands provide excellent platforms for functionalization of N 2 on iron, 60,193,194 and enable characterization of potential N 2 reduction intermediates Fe-N x H y , 98,99,165,194196 including systems that feature a coordinated hydride. 40,42,43 Ammonia production by tripodal trisphosphine ligands with an axial donor (Si, C, or B) increases in the order Si < C < B.…”
Section: Fe-nxhy Complexes With Sulfur Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…17). 61,157,191,192,41,44,165 Peters has shown that phosphine ligands provide excellent platforms for functionalization of N 2 on iron, 60,193,194 and enable characterization of potential N 2 reduction intermediates Fe-N x H y , 98,99,165,194196 including systems that feature a coordinated hydride. 40,42,43 Ammonia production by tripodal trisphosphine ligands with an axial donor (Si, C, or B) increases in the order Si < C < B.…”
Section: Fe-nxhy Complexes With Sulfur Ligandsmentioning
confidence: 99%
“…6 Reviews discussing N 2 reduction by Mo systems, by Fe systems with P and N ligands, and by other metals are available elsewhere. 3744 …”
Section: Introductionmentioning
confidence: 99%
“…Despite intensive efforts for the transformation of dinitrogen gas using transition metal–dinitrogen complexes as catalysts under mild reaction conditions910111213141516, only a few systems have succeeded in the catalytic formation of ammonia from dinitrogen gas171819202122232425262728. In 2003, Yandulov and Schrock29303132 reported the first successful example of the catalytic conversion of dinitrogen gas into ammonia using a molybdenum–dinitrogen complex as a catalyst and in 2013 Peters and co-workers33343536373839 reported the iron-catalysed transformation using an iron–dinitrogen complex as a catalyst.…”
mentioning
confidence: 99%
“…1,2 For example, Cummins has measured the Mo-N triple bond strength in a Mo(NR 2 ) 3 N product of N 2 cleavage to be 155 kcal/mol. 3 Because of the strong metal-nitrogen bonds, the N 2 -derived nitrides often are unreactive toward reagents except high-energy species like silyl halides, 2 acyl halides, 4 and alkyl triflates. 5 Only recently has it become possible to functionalize N 2 with milder reagents like CO and silanes.…”
Section: Introductionmentioning
confidence: 99%